سورة الضحى وتاريخية القرآن في الأدبيات الاستشراقية: Sūrah al-Ḍuḥā and the Qur’anic Historicity in Orientalist Literature - عبد الرحمن عبيد حسين (الدراسات الإسلامية, 2024)
This article critically analyzes the Orientalist scholarship on the Qur’anic Historicity, while particularly focusing on the interpretations of Sūrah al-Ḍuḥā. Orientalists have traditionally dismissed this Sūrah as a "crude primary product" due to its brevity and Meccan origin. They use its ambiguous addressee to support theories of multiple authorship, distinct compositional periods, and external influences. These interpretations often overlook classical Islamic commentaries and the context of revelation (āsbāb al-nuzūl). A key point of contention is the identification of the addressee in Sūrah al-Ḍuḥā. While some Orientalists, such as Rodwell, Bell, and Arberry, followed classical exegesis in linking the pronoun to Prophet Muhammad (peace be upon him), others like Margoliouth, Watt, and Wans Brough have rejected this connection, revealing internal contradictions within Orientalist approaches. This study employs a descriptive-analytical methodology, examining both Orientalist sources and traditional Qur'anic commentaries. The aim is to deconstruct Orientalist interpretations of Sūrah al-Ḍuḥā, exposing their reliance on external sources and their disregard for Islamic scholarly contexts. By scrutinizing the internal inconsistencies and methodological flaws in Oriental scholarship, this research seeks to contribute to a more nuanced understanding of these approaches and their critiques, ultimately demonstrating the value of traditional Islamic scholarship in interpreting the Qur'an and its historical development.